2004
DOI: 10.1161/01.cir.0000138105.17864.6b
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitochondrial Aldehyde Dehydrogenase in Nitroglycerin-Induced Vasodilation of Coronary and Systemic Vessels

Abstract: Background-It has recently been shown that mitochondrial aldehyde dehydrogenase 2 (mtALDH) catalyzes the formation of 1,2-glyceryl dinitrate and nitrite from nitroglycerin (glyceryl trinitrate [GTN]) within mitochondria, leading to production of cGMP and vasorelaxation. However, whether this mechanism operates in the systemic and coronary beds that subserve the antianginal action of GTN is not known. In this study, we address this question in an intact canine model. Methods and Results-Fourteen healthy mongrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 30 publications
6
33
0
Order By: Relevance
“…However, after taking sublingual nitroglycerine, the degree of brachial artery dilatation in patients with the ALDH2 *504Lys allele was significantly lower than in those with the wild-type (Xu et al 2011). These results demonstrate that the ALDH2 *504Lys allele exerts a significant effect on non-endothelium-dependent vasodilation and an insignificant effect on endothelium-dependent vasodilation, which is consistent with previous studies (Zhang et al 2004;Mackenzie et al 2005). Previous studies have confirmed that coronary spasm is significantly correlated with damaged endothelium-but not with non-endotheliumdependent vasodilation.…”
Section: Endothelial Function and Endothelial Nitric Oxide Synthase (supporting
confidence: 93%
See 1 more Smart Citation
“…However, after taking sublingual nitroglycerine, the degree of brachial artery dilatation in patients with the ALDH2 *504Lys allele was significantly lower than in those with the wild-type (Xu et al 2011). These results demonstrate that the ALDH2 *504Lys allele exerts a significant effect on non-endothelium-dependent vasodilation and an insignificant effect on endothelium-dependent vasodilation, which is consistent with previous studies (Zhang et al 2004;Mackenzie et al 2005). Previous studies have confirmed that coronary spasm is significantly correlated with damaged endothelium-but not with non-endotheliumdependent vasodilation.…”
Section: Endothelial Function and Endothelial Nitric Oxide Synthase (supporting
confidence: 93%
“…ALDH2 inhibition can significantly reduce the vasodilatory effects of nitroglycerine (Mackenzie et al 2005;Daiber et al 2009). Another canine study also confirmed that the inhibition of ALDH2 activity can significantly reduce the dilation of canine coronary vessels (Zhang et al 2004). Therefore, regardless of the impact of ALDH2 *504Lys allele on coronary atherosclerosis, the significant activity reduction may decrease the production of vasodilators such as nitric oxide and then induces coronary spasm which triggering ACS occurrence.…”
Section: Endothelial Function and Endothelial Nitric Oxide Synthase (mentioning
confidence: 72%
“…5 could be around 1). Again, our middle dose GTN (10 µg/kg) is similar to that at which cyanamide inhibited the hypotensive effect of GTN in a canine model, 17) which is considered within the range of high affinity pathway.…”
Section: Discussionmentioning
confidence: 82%
“…17) Similarly, it is reported that the vasodilatory effects of GTN and NO 2 − on pulmonary and systemic vascular beds of anesthetized rats were attenuated by cyanamide, while the inhibitor had no effect on SNP-induced vasodilation. 18) The doses of GTN used in the above studies correspond to the middle dose (about 10 µg/kg) that used in the present in vivo study.…”
Section: Discussionmentioning
confidence: 89%
“…Earlier reports described the inhibition of ALDH by organic nitrates, but the pharmacological implications were not considered before the discovery of ALDH2-catalyzed GTN bioactivation in 2002 (Chen et al, 2002;Kollau et al, 2005). Zhang et al (2004) reported that reductants are essential for sustained ALDH2-catalyzed GTN metabolism and bioactivation. Furthermore, Baretta et al (2008) found that GTN biotransformation was promoted by addition of ALDH2 expressed and purified in vitro.…”
Section: Discussionmentioning
confidence: 99%